Targets for improving dispatcher identification of acute stroke. Issue 4 (June 2019) - Mattila, Olli S; Puolakka, Tuukka; Ritvonen, Juhani; Pihlasviita, Saana; Harve, Heini; Alanen, Ari; Sibolt, Gerli; Curtze, Sami; Strbian, Daniel; Pystynen, Mikko; Tatlisumak, Turgut; Kuisma, Markku; et al.
Background: Accurate identification of acute stroke by Emergency Medical Dispatchers (EMD) is essential for timely and purposeful deployment of Emergency Medical Services (EMS), and a prerequisite for operating mobile stroke units. However, precision of EMD stroke recognition is currently modest. Aims: We sought to identify targets for improving dispatcher stroke identification. Methods: Dispatch codes and EMS patient records were cross-linked to investigate factors associated with an incorrect dispatch code in a prospective observational cohort of 625 patients with a final diagnosis of acute stroke or transient ischemic attack (TIA), transported to our stroke center as candidates for recanalization therapies. Call recordings were analyzed in a subgroup that received an incorrect low-priority dispatch code indicating a fall or unknown acute illness ( n = 46). Results: Out of 625 acute stroke/TIA patients, 450 received a high-priority stroke dispatch code (sensitivity 72.0%; 95% CI, 68.5–75.5). Independent predictors of dispatcher missed acute stroke included a bystander caller (aOR, 3.72; 1.48–9.34), confusion (aOR, 2.62; 1.59–4.31), fall at onset (aOR, 1.86; 1.24–2.78), and older age (aOR [per year], 1.02; 1.01–1.04). Of the analyzed call recordings, 71.7% revealed targets for improvement, including failure to recognize a Face Arm Speech Time (FAST) test symptom (21/46 cases, 18 with speech disturbance), or failure to thoroughly evaluate symptoms (12/46 cases). Conclusions: Based on our findings, efforts to improve dispatcher stroke identification should primarily focus on improving recognition of acute speech disturbance, and implementing screening of FAST-symptoms in emergency phone calls revealing a fall or confusion. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02145663.